Decontamination of instruments and control of cross infection in general practice. Issue 6736 (26th May 1990) - Morgan, D R; Lamont, T J; Dawson, J D; Booth, C
Abstract : OBJECTIVE–To assess the effectiveness of decontamination procedures in general practice. DESIGN–Anonymous postal questionnaire survey of 600 general practitioners randomly selected from the national register. SETTING–General practices throughout the United Kingdom. SUBJECTS–382 General practitioners, a response rate of 65%. RESULTS–186 General practitioners had autoclaves but 125 used hot water disinfectors or chemical disinfectants to reprocess instruments. 22% (474/2132) Of high risk instruments were inadequately decontaminated. Decontamination was performed by the practice nurse or receptionist in 306 practices. Knowledge of treatment of spillages of blood fluids was uncertain, and only 114 general practitioners used effective methods for dealing with spillages. CONCLUSIONS–A comprehensive central code of practice for control of infection is needed for primary health care staff.